Non-English primary language and disparities in stroke outcomes after mechanical thrombectomy: a single institution study - Karim, Nurose; Stone, Suzanne; Salter, Amber; Gebreyohanns, Mehari; Johnson, Mark; Jones, Erica (Frontiers in Stroke, 2023)
Background: Delays in acute treatment of ischemic stroke have been associated with worse outcomes. While having a non-English primary language has not been shown to delay receiving thrombolytic therapy, we assessed whether non-English primary language was associated with worse functional outcomes in patients receiving mechanical thrombectomy (MT).Method: This is a retrospective study of our MT database from two comprehensive stroke centers from January 2016 to May 2021. Primary endpoint was discharge modified Rankin Scale (mRS) 0-2. Differences between English primary language (EPL) and non-English primary language (nEPL) groups were evaluated using an analysis of variance (ANOVA), Kruskal-Wallis and chi square test. Multivariable logistic regression was used to evaluate EPL vs nEPL patients using data driven models determined by stepwise selection approach.Result: We identified 276 patients receiving MT with 83% EPL and 17% nEPL patients. nEPL patients had higher mean hemoglobin A1c, were less likely to have insurance, and more likely to have symptomatic intracranial hemorrhage compared to EPL patients (Table ). We observed a longer median ED arrival to groin puncture time in the nEPL group. No differences were observed in discharge or mRS 0-2 in the univariate or multivariable logistic regression. Discussion: Despite finding longer ED length of stay among nEPL patients, there was no difference between nEPL and EPL in good functional outcome rates in patients treated with MT.